Global prevalence, incidence, and outcomes of non-obese or lean non-alcoholic fatty liver disease: a systematic review and meta-analysis. (August 2020) - Ye, Qing; Zou, Biyao; Yeo, Yee Hui; Li, Jie; Huang, Daniel Q; Wu, Yuankai; Yang, Hongli; Liu, Chuanli; Kam, Leslie Y; Tan, Xiang Xuan Eunice; Chien, Nicholas; Trinh, Sam; et al.
Summary: Background: Although non-alcoholic fatty liver disease (NAFLD) is commonly associated with obesity, it is increasingly being identified in non-obese individuals. We aimed to characterise the prevalence, incidence, and long-term outcomes of non-obese or lean NAFLD at a global level. Methods: For this systematic review and meta-analysis, we searched PubMed, Embase, Scopus, and the Cochrane Library from inception to May 1, 2019, for relevant original research articles without any language restrictions. The literature search and data extraction were done independently by two investigators. Primary outcomes were the prevalence of non-obese or lean people within the NAFLD group and the prevalence of non-obese or lean NAFLD in the general, non-obese, and lean populations; the incidence of NAFLD among non-obese and lean populations; and long-term outcomes of non-obese people with NAFLD. We also aimed to characterise the demographic, clinical, and histological characteristics of individuals with non-obese NAFLD. Findings: We identified 93 studies (n=10 576 383) from 24 countries or areas: 84 studies (n=10 530 308) were used for the prevalence analysis, five (n=9121) were used for the incidence analysis, and eight (n=36 954) were used for the outcomes analysis. Within the NAFLD population, 19·2% (95% CI 15·9–23·0) of people were lean and 40·8% (36·6–45·1) were non-obese. The prevalence of non-obese NAFLD in the general population varied from 25% or lower in some countries (eg, Malaysia and Pakistan) to higher than 50% in others (eg, Austria, Mexico, and Sweden). In the general population (comprising individuals with and without NAFLD), 12·1% (95% CI 9·3–15·6) of people had non-obese NAFLD and 5·1% (3·7–7·0) had lean NAFLD. The incidence of NAFLD in the non-obese population (without NAFLD at baseline) was 24·6 (95% CI 13·4–39·2) per 1000 person-years. Among people with non-obese or lean NALFD, 39·0% (95% CI 24·1–56·3) had non-alcoholic steatohepatitis, 29·2% (21·9–37·9) had significant fibrosis (stage ≥2), and 3·2% (1·5–5·7) had cirrhosis. Among the non-obese or lean NAFLD population, the incidence of all-cause mortality was 12·1 (95% CI 0·5–38·8) per 1000 person-years, that for liver-related mortality was 4·1 (1·9–7·1) per 1000 person-years, cardiovascular-related mortality was 4·0 (0·1–14·9) per 1000 person-years, new-onset diabetes was 12·6 (8·0–18·3) per 1000 person-years, new-onset cardiovascular disease was 18·7 (9·2–31·2) per 1000 person-years, and new-onset hypertension was 56·1 (38·5–77·0) per 1000 person-years. Most analyses were characterised by high heterogeneity. Interpretation: Overall, around 40% of the global NAFLD population was classified as non-obese and almost a fifth was lean. Both non-obese and lean groups had substantial long-term liver and non-liver comorbidities. These findings suggest that obesity should not be the sole criterion for NAFLD screening. Moreover, clinical trials of treatments for NAFLD should include participants across all body-mass index ranges. Funding: None.